KONSEP INTERDISIPLINER WACANA BARU NALAR KRITIS MAHASISWA PAI - Damanhuri Damanhuri (STAI Darussalam Lampung, 2024)
This paper aims to discuss the interdisciplinary concept of the new discourse of critical reasoning of PAI students. This research is a literature research, the analysis uses content analysis. The results of the study state that the urgency of the need for science and the conditions that make Muslims shackled require Muslims to be motivated to conduct research with an interdisciplinary approach which is meant here is a study using a number of approaches or points of view (perspectives). in principle, interdisciplinarity efforts involve the integration of two or more disciplines in situations where resources in a single discipline cannot cover the scope of the problem to be solved. This means that when the grand theory of a science has been mastered and is able to create between rationalistic-empiricist with differential planning of learning qur'anic and sunnatik then the output of religion-based schools (Islam) is not in a sceptical frame.